Catalyst-free direct regiospecific multicomponent synthesis of C3-functionalized pyrroles. Issue 29 (1st July 2022) - Pawar, Amol Prakash; Yadav, Jyothi; Dolas, Atul Jankiram; Iype, Eldhose; Rangan, Krishnan; Kumar, Indresh
Abstract : A catalyst-free multicomponent method has been developed for the direct regiospecific synthesis of β-(C3)-substituted N -alkyl/aryl/H-pyrroles in good yields under mild conditions with high atom economy and avoiding protection–deprotection chemistry. Abstract : An operationally simple catalyst-free protocol for the direct regiospecific synthesis of β-(C3)-substituted pyrroles has been developed. The enamine intermediate, in situ generated from succinaldehyde and a primary amine, was trapped with activated carbonyls before the Paal–Knorr reaction in a direct multicomponent "just-mix" fashion to furnish pyrroles with overall good yields. Several C3-substituted N -alkyl/aryl/H pyrroles have been produced under open-flask conditions with high atom economy and avoiding protection–deprotection chemistry.